Aplikasi Prediksi Penjualan Kopi dengan Metode Single Exponential Smoothing untuk Mengetahui Produk Kopi Terlaris - Robby Yuli Endra; Oktavia Laurina (Universitas Bandar Lampung (UBL), 2021)
Indonesia is the fourth-largest coffee exporter in the world. for the Indonesian state, it only focuses on quantity, in fact, the quality of Indonesian coffee has been recognized by various parties in various countries. The majority of the Indonesian population likes coffee, especially the people of Lampung, but only with certain types of coffee such as Arabica, Robusta, etc. Therefore, coffee sellers must provide a stock of various types of coffee products. In the supply of coffee products with various types, it can cause difficulties in providing coffee products and effective storage so that the existing products are preserved and the quality of taste is maintained. The provision of coffee products is carried out using estimates without any definite calculations and also the seller has not been able to predict the coffee products that are often in demand by consumers. Based on the problems experienced, we need a method that is able to predict the coffee products that will be sold a lot, so that there is no accumulation of product stock. One method that can help solve this problem is to use the single exponential smoothing method. Single exponential smoothing is one of the existing methods in the forecasting (prediction) system. By looking at the problems and methods that have been determined to solve the problems, this research will build a forecasting application (prediction). This system can help sellers in predicting coffee product sales. So that sellers can find out which coffee products will be selling well and can prepare the amount of coffee availability that customers are interested in.